Application of Stack Data Structure in Application Development - Amaylia, Sarah; Viktoria Angelita Setiabud; Renza Alvianino; Rahmat Nugroho Saputra; Helena Kusuma Wardhani; Azis Suroni (Journal of Advanced Systems Intelligence and Cybersecurity, 2025)
The rapid development of digital technology has driven the need for efficient, modular, and maintainable applications. In this context, the stack data structure plays a crucial role in supporting the development of responsive and structured applications. This article discusses the application of the stack data structure in various aspects of application development, both conceptually and technically. The method used is a literature review, analyzing nine scientific journals as the basis for the study. The results indicate that the stack is not only theoretically relevant as a Last-In First-Out (LIFO) structure but also proven effective in implementing various application features, such as user navigation, undo-redo systems, mathematical expression processing, and graph traversal. Stacks can be implemented using arrays or linked lists, depending on the requirements for flexibility and memory efficiency. Considering its ease of implementation and wide range of real-world applications, the stack data structure becomes an important component for developers to master. Proficiency in stack concepts and practices directly contributes to improving the quality of applications built.